PENGARUH HASIL BELAJAR MENGGUNAKAN MODEL CONTEXTUAL TEACHING AND LEARNING PADA MATEMATIKA - Hartanti, Khusnul Tri; Basir, Udjang Pairin M.; Susilo, Claudya Zahrani (Prodi PGSD Fakultas Ilmu Pendidikan (FIP) Universitas Hasyim Asy'ari (Unhasy) Tebuireng Jombang, 2020)
Many students find it difficult to accept fraction material from the teacher because student are more receptive to material through the surrounding environment such as fruit, bread, marbles, stones, etc. The purpose of this researchs to determine student learning outcome whether thereis influence when use the Contextual Teaching and Learning (CTL) model of mathematics subject matter in the 4th grade SDN Jombatan IV Jombang. This type of research is PreExperimental Design, the design used is one-group pretest -posttest design. The study focus on student learning outcomes in fraction material with the CTL model. Based on research that has been done, it can seen than more than 90% of students can achieve KKM value. In testing the test-t if the value of t is greater than t table then the hypothesis is accepted. It is evident from the results of the study that tcount = 5.344219271 and ttable = 2.178812827, which means that it has a strong signification shows that there is an influencer on student learning outcomes. The one-party test, it turns out that tcount falls in the area of acceptance of Ha, which the result test shows menunjukkan thitung Ëƒ ttabel so that the conclusion are Ha is accepted and Ho is rejected. So it can be said that learning uses Contextual Teaching and Learning (CTL) can affect of student learning outcomes.